Comparison of dermatoglyphic patterns in oral leukoplakia and oral submucous fibrosis patients - Kulkarni, Venkatesh V.; Chaudhari, Aditi R.; Kulkarni, Aishwarya S. (International Journal of Research in Medical Sciences, 2019)
Background: Genetics plays an important role in the detection of an Oral potentially malignant lesion. A major contributor to genetic study is Dermatoglyphics or the study of fingerprints and lines of palmer and plantar surfaces. Many researchers have used dermatoglyphics to connect genetics with oral lesions and malignancies. Thus, the current study has been conducted to find out an association between dermatoglyphic patterns and oral leukoplakia, oral submucous fibrosis and healthy subjects. Methods: The present study is conducted on subjects that have been already diagnosed with oral lesions. Fingerprint patterns (whorled, loop and arch) were evaluated by utilizing fingerprints. Results: The present study showed that the loop pattern was common in all three subjects. The frequency of whorled and arch pattern is decreased in oral leukoplakia and oral submucous fibrosis that healthy subjects. Arch pattern is comparatively decreased in subjects with oral leukoplakia than oral submucous fibrosis and there is a decrease in the frequency of whorled patterns in OSMF as compared to oral leukoplakia. Conclusions: Authors conclude that simply by observing the whorled and arch patterns in a subject, authors can hypothesize that risk of occurrence of oral leukoplakia and oral submucous Fibrosis and take preventive measures against the said lesions.